The Teenage Worrier's Pocket Guide To Success (Teenage Worrier's Pocket Guides) - Asquith, Ros (Transworld Publishers Ltd, 1998)
Failing? Ailing? Always wailing? WORRY NO MORE! I, moi, me, Letty Chubb, aged 15, werld famous author of WORRY-FREE bukes of TRUE TEENAGE WORRIERS, am on YOUR SIDE! Here, within this V. nice cheap, pocket-sized guide is LOTS of v. interesting stuff about, er... SUCCESS... from Acting to Zest...
Keywords: Success In Adolescence; Teenagers